SEJARAH DAN KEDUDUKAN HUKUM ADAT DALAM PEMBANGUNAN HUKUM NASIONAL - Miftahuddin, Abdul Hafidz; Shukia , Ayun (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2024)
Indonesian society encompasses a diversity of ethnicities, religions, and cultures, which have formed a unity within the Unitary State of the Republic of Indonesia. Customary law is a system of unwritten social control that is important in society to provide characteristics and identity to the nation. The concept of customary law in Indonesia originates from the term